1981
DOI: 10.1111/j.0033-0124.1981.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Any Place but Here! Mental Health Facilities as Noxious Neighbors

Abstract: This paper describes an experimental study that attempts to uncover some of the reasons why community residents find mental health facilities undesirable as potential neighbors. Respondents were asked to evaluate a variety of public facilities by indicating how similar they are in terms of “noxiousness.'’They were also asked how close they would prefer to live to each of the different facility types. From the results of the study it is possible to suggest some alternative strategies for siting new mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Questions of equality in terms of gender, race and class were prominent, with a broad emancipatory drive to highlight inequalities in the provision of care, particularly with regard to the shift from mass hospitalisation to community service provision (Wolch & Philo, 2000). Analysis of the social effects of the locating of new community services occurred, incorporating the views of the general public faced with the prospect of having 'mad' neighbours (Dear & Taylor, 1982;Smith & Hanham, 1981a, 1981b. A concern with analysing the perspectives of the mentally distressed themselves arose, with those actually using services rather than the services themselves becoming a research priority.…”
Section: Community Mental Health and Home Spacesmentioning
confidence: 99%
“…Questions of equality in terms of gender, race and class were prominent, with a broad emancipatory drive to highlight inequalities in the provision of care, particularly with regard to the shift from mass hospitalisation to community service provision (Wolch & Philo, 2000). Analysis of the social effects of the locating of new community services occurred, incorporating the views of the general public faced with the prospect of having 'mad' neighbours (Dear & Taylor, 1982;Smith & Hanham, 1981a, 1981b. A concern with analysing the perspectives of the mentally distressed themselves arose, with those actually using services rather than the services themselves becoming a research priority.…”
Section: Community Mental Health and Home Spacesmentioning
confidence: 99%
“…Neighborhood characteristics have often been used as predictors of acceptance (Sigelman 1976;Segal et al 1980;Green, McCormick, and Walkey 1987;Gale, Ns, and Rosenblood 1988). With respect to mental disability, for example, accepting neighborhoods have been characterized by large proportions of unmarried, younger, and renting individuals (suggesting a more transient population); rejecting communities have been more homogeneous in terms of race, income, and education (Trute and Segal 1976;Smith and Hanham 1981). Suburban communities, in particular, have been identified as commonly rejecting controversial human service facilities (Taylor, Dear, and Hall 1979).…”
Section: Explaining Community Oppositionmentioning
confidence: 99%
“…Research has demonstrated however that mental health facilities, now frequently situated in central-urban locations, are categorized as ''noxious'' by communities (see Moon, 1988). Smith and Hanham (1981) found that this level of noxiousness was only slightly better than ''sewage plants' ' and ''prisons''. Findings therefore indicate that facility anonymity is beneficial for service-users (Huxley et al, 1990;Huxley, 1993).…”
Section: Introductionmentioning
confidence: 88%